Representations for the generalized inverses of a modified operator - Mosić, D. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
Some explicit representations for the generalized inverses of a modified operator A + YGZ are derived under some conditions, where A, Y, Z, and G are operators between Banach spaces. These results generalize the recent works about the Drazin inverse and the Moore – Penrose inverse of complex matrices and Hilbert-space operators.